POLITICAL CULTURE OF BAHUJAN SAMAJ PARTY: FROM THE TIME OF ITS INCEPTION TO 2020 - Jaiswal, Rakesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Political culture includes the attitudes, beliefs, dedication and values ​​of the people of a country towards its political system. In other words, the political beliefs, feelings and attitudes of the people in the context of the political system are collectively called political culture. Political culture is an important and new approach of modern political science. It is an attempt to integrate psychology and sociology so that political analysis can be used correctly. The advent of political culture has been accepted in the literature of political science since 1956. According to Almond and Powell, "Political culture includes such attitudes, beliefs, values ​​and art which are prevalent in the entire population. It also includes those tendencies and patterns which are found in different parts of that population." According to Lucian Pye, "Political culture is a group of attitudes, beliefs and sentiments which give order and meaning to political knowledge and which provide the underlying assumptions and rules on the basis of which the behaviour of the political system is controlled. Political ideals and the prevalent characteristics of the political system also come under its ambit. Thus, political culture is a collective expression of psychological and subjective moments." According to Finer, "The political culture of a nation mainly reveals the legitimacy of rulers, political institutions and political processes."